Electoral judge as political communicator - Brenes Villalobos, Luis Diego (2014)
This study pretends to examine the Costa Rican electoral judge’s behavior as a political communicator. Precisely, it looks at which measures this judge has adopted in order to contribute to a better exposition, circulation and comprehension of the rulings he delivers. To this purpose, the article looks over the evolution and changes in the communicational actions of the Costa Rican electoral judge during the nineties and it’s divided in four sections: 1) Brief introduction regarding the communicative responsiveness; 2) Institutional Political Communication; 3) Training, Web and Social Networks; 4) Corollary.